2009
DOI: 10.2320/matertrans.m2009236
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Assisted Hydrothermal Synthesis of In(OH)<SUB>3</SUB> Nanoparticles Controlled in Size and Shape

Abstract: Size and shape controlled indium hydroxide (In(OH) 3 ) nanoparticles are readily obtained by amino acid assisted hydrothermal synthesis from an aqueous system. The shape control is achieved by the utilization of adsorption of amino acid on the growing surfaces of the nanoparticles, and rod-and cubic-shaped In(OH) 3 nanoparticles are selectively formed in the presence of glycine and L-aspartic acid, respectively. Furthermore, by utilization of two-step aging technique in L-aspartic acid system, originally devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…Recently, we have reported the size and shape control of In(OH) 3 nanoparticles by an amino-acid assisted hydrothermal method. 27 Cubic-shaped In(OH) 3 nanoparticles with the size of 50 nm were formed by addition of aspartic acid in the reaction solution. Hence, size-and shape-controlled In(OH) 3 nanoparticles have been successfully prepared; however, the further thermal treatment is inescapable to obtain ITO nanoparticles, because the In(OH) 3 phase formed in the aqueous system is rather stable even with increasing the aging temperature up to 250 C.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have reported the size and shape control of In(OH) 3 nanoparticles by an amino-acid assisted hydrothermal method. 27 Cubic-shaped In(OH) 3 nanoparticles with the size of 50 nm were formed by addition of aspartic acid in the reaction solution. Hence, size-and shape-controlled In(OH) 3 nanoparticles have been successfully prepared; however, the further thermal treatment is inescapable to obtain ITO nanoparticles, because the In(OH) 3 phase formed in the aqueous system is rather stable even with increasing the aging temperature up to 250 C.…”
Section: Introductionmentioning
confidence: 99%
“…34,35 In our previous studies, we reported the solvothermal synthesis of ITO NPs with a cubic shape, 36,37 a narrow size distribution, 38 and protrusions on the NP surface; 39 in contrast, only indium hydroxide (In(OH) 3 ) NPs with a cubic shape were formed, and no ITO NPs were obtained when hydrothermal NP synthesis was conducted. 40 In the case of ZO, AZO, and/or GZO NPs, 41 solvothermal methods 42 in ethanol, 43−47 benzyl alcohol, 48 and methoxyethanol 47 have been reported. Regarding the application of nanoink-coating methods to prepare TCO films, the particle mean size of AZO and GZO reported in previous studies 43,44,46 was too large to prevent light scattering, thus reducing transparency in the visible light region.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Namely, we have reported the size and shape control of In(OH) 3 nanoparticles by aminoacid assisted hydrothermal method. (Sasaki et al, 2009). Cubic-shaped In(OH) 3 nanoparticles with the size of 50 nm were formed by addition of aspartic acid in the reaction solution.…”
Section: Introductionmentioning
confidence: 99%